The Effects of Multiple Minimum Wages Throughout the Labor Market - Katherine Terrell; T. H. Gindling (Institute for the Study of Labor (IZA), 2004)
This paper investigates the effects of legal minimum wages on wages, employment, hours worked and monthly earnings among workers covered by minimum wage legislation as well as those for whom it does not apply (the uncovered sector) in Costa Rica. This country?s large uncovered sector and complex minimum wage policy, which has for decades set numerous wages throughout the wage distribution, provide a stimulating counterpoint to the U.S. framework for the analysis of the impact of minimum wages. We find that legal minimum wages have a significant positive effect on the wages of workers in the covered sector (with an elasticity of 0.10) but no effect on wages of workers in the uncovered sector. We also find that a 10% increase in minimum wages lowers employment in the covered sector by 1.09% and decreases the average number of hours worked of those who remain in the covered sector by about 0.6%. Finally, we show that despite the wide range of minimum wages, the largest impact on the wages and employment of covered sector workers is in the lower half of the distribution.
Keywords: J38; J31; J23; 330; minimum wages; employment; wages; Costa Rica; Mindestlohn; Wirtschaftspolitische Wirkungsanalyse; Lohnstruktur; Beschäftigungseffekt; Einkommensverteilung; Schätzung; Costa Rica